2020
DOI: 10.1080/13880209.2020.1803367
|View full text |Cite
|
Sign up to set email alerts
|

2,3,5,4′-Tetrahydroxy-stilbene-2-O-beta-d-glucoside induces autophagy-mediated apoptosis in hepatocytes by upregulating miR-122 and inhibiting the PI3K/Akt/mTOR pathway: implications for its hepatotoxicity

Abstract: Dai (2020) 2,3,5,4′-Tetrahydroxy-stilbene-2-O-beta-d-glucoside induces autophagymediated apoptosis in hepatocytes by upregulating miR-122 and inhibiting the PI3K/Akt/mTOR pathway: implications for its hepatotoxicity,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…THSG treatment has been proven to induce autophagy by upregulation of autophagy-related proteins Beclin 1, LC3-II, and ATG12 in the liver tissues of prediabetic rats (Wang et al, 2020). It was also reported that THSG significantly induced autophagy and increased the expression of LC3-II protein in human WRL-68 hepatic cells (Yang et al, 2020). Consistent with those reports above, our results revealed that THSG treatment dramatically increased the protein levels of Beclin 1 and LC3B-II in TGF-β1stimulated MRC-5 human lung fibroblast cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…THSG treatment has been proven to induce autophagy by upregulation of autophagy-related proteins Beclin 1, LC3-II, and ATG12 in the liver tissues of prediabetic rats (Wang et al, 2020). It was also reported that THSG significantly induced autophagy and increased the expression of LC3-II protein in human WRL-68 hepatic cells (Yang et al, 2020). Consistent with those reports above, our results revealed that THSG treatment dramatically increased the protein levels of Beclin 1 and LC3B-II in TGF-β1stimulated MRC-5 human lung fibroblast cells.…”
Section: Discussionmentioning
confidence: 95%
“…Accumulating evidence has also shown that the repression of TGF-β1-induced activation of mTOR signaling in lung fibroblasts, which results in the induction of autophagy and the inhibition of myofibroblast activation and ECM production in mice model of BLM-induced pulmonary fibrosis ( Li et al, 2021 ; Lu et al, 2022 ). Furthermore, THSG has been demonstrated to trigger autophagy in human hepatocytes via the inhibition of the PI3K/Akt/mTOR signaling pathway ( Yang et al, 2020 ). Herein, these findings indicate that THSG inhibits the TGF-β1-induced Akt/mTOR pathway in human lung fibroblasts and alveolar epithelial cells, thereby leading to autophagy activation and subsequent alleviating lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%